2022
DOI: 10.3346/jkms.2022.37.e154
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Polyangiitis Following mRNA COVID-19 Vaccination: A Case Report

Abstract: Coronavirus disease 2019 (COVID-19) is one of the most widespread viral infections in human history. As a breakthrough against infection, vaccines have been developed to achieve herd immunity. Here, we report the first case of microscopic polyangiitis (MPA) following BNT162b2 vaccination in Korea. A 42-year-old man presented to the emergency room with general weakness, dyspnea, and edema after the second BNT162b2 vaccination. He had no medical history other than being treated for tuberculosis last year. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…These results should be interpreted with caution as a meta-analysis published later found no association between HPV vaccination and autoimmunity [45]. There are a few recent studies, mostly case-control studies, reporting induction of various autoimmune diseases in individuals after vaccination with BNT162b2, including rheumatoid arthritis [46], ANCA-associated vasculitis [47,48], and microscopic polyangiitis [49].…”
Section: Discussionmentioning
confidence: 87%
“…These results should be interpreted with caution as a meta-analysis published later found no association between HPV vaccination and autoimmunity [45]. There are a few recent studies, mostly case-control studies, reporting induction of various autoimmune diseases in individuals after vaccination with BNT162b2, including rheumatoid arthritis [46], ANCA-associated vasculitis [47,48], and microscopic polyangiitis [49].…”
Section: Discussionmentioning
confidence: 87%
“…Elevated MPO antibodies and histological findings lead to the diagnosis of MPA. After receiving glucocorticoid therapy, rituximab, and plasma exchange, the patient’s symptoms improved [ 129 ]. However, the exact mechanism by which COVID-19 vaccines induce AAV is not yet well understood.…”
Section: Resultsmentioning
confidence: 99%
“…These authors also observed the reduction of the ANCA response to the RNA vaccine once it was treated with ribonuclease. ANCA vasculitis has been reported in connection with COVID-19 infection and the different types of vaccination to prevent it [2][3][4][5][6]17,18], prompting the suspicion of whether the immunological phenomenon is a direct result of the mRNA content of the vaccine. Hypothesized mechanisms like molecular mimicry, defective neutrophilic apoptosis, polyclonal activation, and a systemic proinflammatory cytokine response can explain the temporal causal association between autoimmune manifestations of ANCA vasculitis and COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…As vaccination rates increase, rare side effects begin to emerge. Cases of small-vessel vasculitis have been reported following the administration of the different COVID-19 vaccines [2][3][4][5][6][7][8][9][10]. Only a few instances of microscopic polyangiitis (MPA) following Pfizer-BioNTech mRNA vaccine administration have been reported in English literature [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation